Go Green: The Anti-Inflammatory Effects of Biliverdin Reductase - Wegiel, Barbara; Otterbein, Leo (Frontiers in Pharmacology, 2012)
Biliverdin (BV) has emerged as a cytoprotective and important anti-inflammatory molecule. Conversion of BV to bilirubin (BR) is catalyzed by biliverdin reductase (BVR) and is required for the downstream signaling and nuclear localization of BVR. Recent data by others and us make clear that BVR is a critical regulator of innate immune responses resulting from acute insult and injury and moreover, that a lack of BVR results in an enhanced pro-inflammatory phenotype. In macrophages, BVR is regulated by its substrate BV which leads to activation of the PI3K-Akt-IL10 axis and inhibition of TLR4 expression via direct binding of BVR to the TLR4 promoter. In this review, we will summarize recent findings on the role of BVR and the bile pigments in inflammation in context with its activity as an enzyme, receptor and transcriptional regulator.